1991
DOI: 10.1111/j.1365-2427.1991.tb01411.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chemistry and habitat features on the microcrustacea of some upland Welsh streams

Abstract: 1. Microcrustaceans were sampled during September 1990 from three microhabitats (margins, stony riffles and gravel) at thirteen stream sites in mid-Wales.2. Patterns in the distribution, abundance and community structure of microcrustacean taxa were related to stream chemistry, physiography, substratum composition and marginal habitat structure. Patterns of distribution between microhabitats were also assessed.3. Chemical variables were the strongest correlates with microcrustacean parameters. Total numbers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
2
15
0
1
Order By: Relevance
“…Marcarelli et al (2011) similarly found that food quality can be more important than quantity of standing crop in driving ecosystem productivity. Second, defended taxa, including both Potamopyrgus and Ostracoda, have been reported to dominate in areas with high macrophyte biomass (Rundle and Ormerod 1991, Humphries et al 1996, Collier et al 1999, Jaschinski et al 2011), which we observed in this study as well.…”
Section: Community Composition and Trophic Interactionssupporting
confidence: 76%
“…Marcarelli et al (2011) similarly found that food quality can be more important than quantity of standing crop in driving ecosystem productivity. Second, defended taxa, including both Potamopyrgus and Ostracoda, have been reported to dominate in areas with high macrophyte biomass (Rundle and Ormerod 1991, Humphries et al 1996, Collier et al 1999, Jaschinski et al 2011), which we observed in this study as well.…”
Section: Community Composition and Trophic Interactionssupporting
confidence: 76%
“…Among abiotic factors, pH plays an important role in the species composition of benthic copepod assemblages (Rundle & Hildrew, 1990;Rundle & Ormerod, 1991;Fryer, 1993a,b) and circumneutral conditions harbour the highest species richness (Fryer, 1980). However, species densities of Moraria brevipes are negatively correlated with pH (Rundle, 1990).…”
Section: Physical and Chemical Requirementsmentioning
confidence: 99%
“…Studies focussed on the spatial and temporal distribution of riverine microorganisms have essentially examined only the phytoplankton and zooplankton communities (Rzoska, 1968;Saunders & Lewis, 1988;Brown et al, 1989;Hamilton et al, 1990;Rundle & Ormerod, 1991;Vranosky´, 1995;Pourriot et al, 1997;Reckendorfer et al, 1999;Viroux, 1999) and, to our knowledge, bacteria, heterotrophic flagellates or ciliates have not been documented together with the other components of the plankton.…”
Section: Introductionmentioning
confidence: 97%